5g+4c+20=0

Simple and best practice solution for 5g+4c+20=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5g+4c+20=0 equation:


Simplifying
5g + 4c + 20 = 0

Reorder the terms:
20 + 4c + 5g = 0

Solving
20 + 4c + 5g = 0

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-20' to each side of the equation.
20 + 4c + -20 + 5g = 0 + -20

Reorder the terms:
20 + -20 + 4c + 5g = 0 + -20

Combine like terms: 20 + -20 = 0
0 + 4c + 5g = 0 + -20
4c + 5g = 0 + -20

Combine like terms: 0 + -20 = -20
4c + 5g = -20

Add '-5g' to each side of the equation.
4c + 5g + -5g = -20 + -5g

Combine like terms: 5g + -5g = 0
4c + 0 = -20 + -5g
4c = -20 + -5g

Divide each side by '4'.
c = -5 + -1.25g

Simplifying
c = -5 + -1.25g

See similar equations:

| -0.77y=6 | | 2(3x+5)=6x+5 | | 4-6x=10-8x | | B+19=128 | | 2(3x+5x)=6x-7x | | 6t-15=5t+12 | | 2(4x+6)=24 | | 13(t-6)=65 | | 2(4+6)=24 | | 0.22u=-2 | | 0.23u=-2 | | 6(2y-5)=-66 | | 5-[2-(-4)-6]= | | y^2-3y-90=0 | | -3+(-7)+8= | | 7w=2 | | 8+(-2)+(-9)= | | 42-(-25)= | | -6-2x+3=-18x+7-2x | | -6-(-30)= | | 15-[8-(-3)+14-7]-(-10)= | | 16s^2+56st+49t^2= | | 2x-7(1-6x)=7 | | 3x^2+30x=24 | | x^2+y^2+2y=63 | | 199-3x=42x+24 | | -.80+.60=-1.67v+.34v | | 7+2x=2-(4x+7) | | p(x)=6x^2+4x | | 2+5-7=2 | | -4x+5=-11 | | X-8=160 |

Equations solver categories